2009
DOI: 10.1111/j.1600-051x.2009.01448.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal health, oral health behaviours, and chronic obstructive pulmonary disease

Abstract: Poor periodontal health, dental care, and oral health knowledge were significantly associated with an increased risk of COPD. Our findings indicate the importance of promoting dental care and oral health knowledge that can be integrated into the prevention and treatment of COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
104
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(125 citation statements)
references
References 19 publications
(29 reference statements)
15
104
2
4
Order By: Relevance
“…Therefore, the improvement in the total score obtained in the SGRQ after one year indicate that phase I periodontal treatment significantly influences the quality of life in COPD patients. This supports the findings of Wang et al, (2009) 11 and Zhou et al, 19 , who have suggested that promoting dental care and oral health knowledge may improve the quality of life in COPD patients. Thus, the findings of the present study suggest that phase I periodontal therapy may play an important role in improving the quality of life in COPD patients.…”
Section: Results and Observationssupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, the improvement in the total score obtained in the SGRQ after one year indicate that phase I periodontal treatment significantly influences the quality of life in COPD patients. This supports the findings of Wang et al, (2009) 11 and Zhou et al, 19 , who have suggested that promoting dental care and oral health knowledge may improve the quality of life in COPD patients. Thus, the findings of the present study suggest that phase I periodontal therapy may play an important role in improving the quality of life in COPD patients.…”
Section: Results and Observationssupporting
confidence: 91%
“…This may due to the phase 1 therapy carried out in group B and progressive nature of the periodontal disease, if not treated and lack of oral health knowledge Wang et al, 11 .In this study, it has been found that the SGRQ symptom score, activity score, impact score and total score are decreased in group B from day 0 to after one year, in contrast of group A where all the parameters are increased. The differences were found to be statistically significant when compared between group B and group A at the end of one year.…”
Section: Results and Observationsmentioning
confidence: 55%
See 1 more Smart Citation
“…Our previous study showed that CP is positively related to COPD (3). The severity of CP in patients with accompanying COPD was greater than that in patients without COPD.…”
Section: Introductionmentioning
confidence: 86%
“…More speciically, patients with COPD had a higher dental plaque index, and an insuicient support of the tooth from the surrounding tissues. Moreover, the same patients had an unsatisfactory behavior regarding their oral hygiene, as measured by the frequency of toothbrushing, the use of dental yarns, and the frequency of visits to the dentist [21]. In another study, a direct correlation between COPD severity and poor hygiene was found in general.…”
Section: Epidemiology Of Copd and Periodontitismentioning
confidence: 91%